Physiological and phytosanitary potential of cucumber seeds - Vieira, Jucilayne Fernandes; Rufino, Cassyo de Araújo; de Oliveira, Lucicléia Mendes; Figueiredo Neto, Acácio; Villela, Francisco Amaral; Barros, Antonio Carlos Souza Albuquerque (MAGISTRA, 2018)
Abstract: Cucumber is a very important crop produced and consumed in Brazil. Its seeds have high commercial value and deserve special attention due to their physiological and sanitary quality. Therefore, studies aiming at determining seed vigor should be intensified because the germination test used for assessing the quality of seeds often shows no correlation with field emergence. The present study was carried out to evaluate the physiological and sanitary qualities of cucumber seed lots. The study was conducted at the Laboratory of Seed Analysis and at the greenhouse of the Department of Plant Science, at the Universidade Federal de Pelotas (UFPel). Four lots of cucumber seeds, cultivar ‘Aoidai’, were tested for the following features: germination, first count germination, accelerated aging, electrical conductivity, cold test, sanitary condition, and seedling emergence. The experimental design was completely randomized with four replications. Means were compared by Tukey test at 5% probability. It was concluded that the accelerated aging test showed efficiency to evaluate the physiological quality of cucumber seeds. However, the cold test, with evaluations at 3 and 5 days, proved to be the most efficient for distinguishing differences in vigor levels between the seed lots.The incidence of fungi associated with seeds of cucumber do not affect the physiological quality of the lots. Keywords: Cucumis sativus L., Vigor, Vegetable.